To Synthesize Hydroxyapatite by Modified Low Temperature Method Loaded with Bletilla striata Polysaccharide as Antioxidant for the Prevention of Sarcopenia by Intramuscular Administration - Ya-Jyun Liang; Jia-Yu Hong; I-Hsuan Yang; Xin-Ran Zhou; Yi-Wen Lin; Tzu-Chieh Lin; Chun-Han Hou; Feng-Huei Lin (Antioxidants, 2021)
Oxidative stress has been suggested as an important factor in the progress of sarcopenia. The current treatments for sarcopenia have the disadvantages of insufficient effect or daily administration. Therefore, an alternative for effective, safety and long-term treatment may be a solution for unmet needs. Bletilla striata polysaccharide has been reported to have antioxidative and anti-inflammatory properties. In this study, we used Bletilla striata polysaccharide (BSP) combined with hydroxyapatite, a carrier. We hypothesized that the resulting combination (BSP-HAP) is a good formula for the controlled release of BSP via intramuscular (IM) administration, so as to prevent the worsening of presarcopenia or even recover from the early stage of the illness. In this research, BSP-HAP was synthesized by a modified low temperature co-precipitation process that would be beneficial for BSP loading. By conducting DCFDA, WST-1 and the Live/Dead assay, BSP-HAP is shown to be a biocompatible material which may release BSP by cells through the endocytosis pathway. Animal studies revealed that the rats treated with BSP-HAP could effectively recover muscle endurance, grip strength or fat/lean mass ratio from lipopolysaccharide (LPS)-induced sarcopenia. This study shows BSP delivered by BSP-HAP system has potential for application in the treatment and prevention of sarcopenia in the future.